Design a Flood Detection Device Using Virtuino-based HC-SR04 Sensor - Dahlan Abdullah; Andik Bintoro; Cut Ita Erliana; Muhammad Fauzan (Majlesi Journal of Electrical Engineering)
The flood detection tool uses the HC-SR04 sensor made specifically to detect the water level in the river. This tool is a series of simple tools that utilize the esp32 microcontroller and media monitoring in real time via a smartphone. The flood detection tool using the HC-SR04 sensor consists of a tool frame made of iron, the HC-SR04 sensor and a panel box. The main power source for this tool is a 12 V 5 Ah battery that comes from a 50wp solar panel. This tool is equipped with various electronic components including an LCD, HC-SR04 sensor, relay and stepdown module. The designed tool will be placed on the riverbank, the HC-SR04 sensor acts as a real time measure of water level. When the sensor has detected a predetermined water level, the sensor will send data to the microcontroller. The microcontroller will process the data and send it to the virtuino application which will display it virtually on the smartphone. Along with this, the data will also be displayed on the LCD.